Response–Response Binding: New Evidence from Event-Related Potentials Data - Biye Wang; Lu Wang; Tao Tao; Wei Guo (Brain Sciences)
Background: Response–response (RR) binding, involving the integration of independently planned and executed responses, presents a novel perspective on action control. While behavioral evidence on RR binding has been extensively examined, corresponding electrophysiological evidence remains scarce. This study aims to contribute novel insights into RR binding by event-related potentials (ERP) techniques to provide new evidence for RR binding. Methods: An adapted prime-probe paradigm was employed, in which the required responses could either involve repetition or change conditions from the prime to the probe phase. EEG data were collected from thirty-six participants, and ERP analysis focused on the peak amplitude and latency of the P1 and P3 components. Results: Notably shorter RTs were observed in the response–repetition conditions compared to others, consistent with previous findings on RR binding. Furthermore, the response–repetition conditions exhibited larger P3 amplitudes and shorter P1 and P3 latencies relative to other conditions. Conclusions: In summary, this study strengthens the evidence base for RR binding by bridging both behavioral and electrophysiological perspectives.